SCOP: A sequential constraint-free optimal control problem algorithm - Rousseau, G.; Tran, Q.H.; Sinoquet, D. (2008 Chinese Control and Decision Conference, 2008)
In this paper, we propose a new computational algorithm for optimal control problems with a scalar state subject to simple-bound constraints. Unlike multiple shooting algorithms, the number of active constraints does not need to be known in advance. This method is also much faster than dynamic programming. Convergence is proved for two particular cases. SCOP is applied for an optimization problem of fuel consumption for a hybrid vehicle.